Covariational reasoning of field dependent prospective mathematics teacher in solving covariance problem - Rahman, Fatchiyah; Juniati, Dwi; Siswono, Tatag Yuli Eko (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
This study aims to analyze the coordination and construction aspects of covariational reasoning of field dependent students’ prospective mathematics teachers in solving covariation problems. This research is qualitative research with the subject of research being field dependent prospective mathematics teachers of STKIP PGRI Jombang. The instruments in this study are the main instrument (the researcher himself) and supporting instruments in the form of GEFT, Covariation Test, and interview guidelines. Data analysis uses data reduction steps, data presentation, and conclusions. Based on the results of the study, the subjects coordinate the magnitude of variable changes and determine the pattern of change for linear covariation problems based on calculations from the results of the representation of covariation task-based problems to compile their change patterns, for linear students using students' own understanding without doing calculations. In the construction aspect, the subject constructs through the representation of the relationship of two variables into a graph by determining the coordinate axis with known variables and drawing a graph from the results of calculating the pattern of change in the relationship of two variables. From the depicted graph, the direction of the chart can be determined. The resulting graph corresponds to a given covariation task-based problem.